Pengaruh Kualitas Produk dan Kualitas Pelayanan terhadap Keputusan Pembelian di Optik Sejahtera Depok - Pasaribu, Veta Lidya Delimah; Setiawan, Redy (AKADEMIK: Jurnal Mahasiswa Ekonomi & Bisnis, 2024)
The aim of this research is to obtain the necessary data and information and process it as comparison material with theories from library research to fulfill the requirements for writing a dissertation. find out how product quality influences purchasing decisions and find out how service quality influences purchasing decisions at Optik Sejahtera Depok. As well as to find out simultaneously the influence of product quality and service quality in purchasing decision making at Optik Sejahtera Depok. The following research analysis uses a quantitative approach analysis and the research population includes a purchasing decision population of 312 people. 76 The sample used in this research, the sampling technique used is non-probability, the sampling technique used is purposive sampling, and the determination formula The sample size is considered appropriate to represent the entire population, the Slovin formula is used, and the maximum margin is used. The maximum error or error is used. This formula sets the acceptable value to be 0.10 or 10% or 76 respondents. Product quality results can have a significant impact on purchasing decisions because the t count is 2.204 > 1.992 in the t table, and sig.< 0> t table 1.992 and the Sig. < 0> Table 3.12 and Sig value. <;0.05 (0.000 <0.05).